Teacher Needs Analysis as a Basis for Developing CPS-EIS Based E-Module in Environmental Change Learning - Endah Pratiwi; Baskoro Adi Prayitno; Umi Fatmawati (FKIP - Universitas Riau, 2026)
The global environmental crisis positions the education sector as a strategic actor in mitigation and adaptation efforts. This study analyzes biology teacher needs to establish a foundation for developing an e-module based on the Collaborative Problem Solving Environmental Issue-Based Socio-Scientific Issues (CPS-EIS) framework. Through a descriptive research design, data were obtained from practitioners using a validated five-level Likert scale instrument. Evidence indicates a high priority for digital media that integrates authentic environmental cases and guides systematic collaborative thinking processes over simple information delivery. The integration of the CPS-EIS model offers a novel solution by aligning collaborative group work with the analysis of controversial socio-scientific issues to address the disparity between curriculum objectives and field realities. These results serve as the primary guideline for the instructional design of adaptive tools intended to improve environmental literacy and student collaboration in high school settings.